Sucrose enhanced stigmasterol production in callus cultures of Wedelia biflora (L.) D.C - Idris, Siti Norayu; Ahmed, Abdul Bakrudeen Ali; Taha, Rosna Mat (College of Agriculture and Food Science, University of the Philippines Los Banos, 2018)
Callus culture method was used to extract stigmasterol in mass amount. The current study aims to enhance the production of stigmasterol by manipulation of sucrose concentrations in Murashige and Skoog (MS) media. A combination of 2 mg NAA L-1 (an auxin) and 2.5 mg 6-benzylaminopurine (BAP) L-1 (a cytokinin) in MS medium was the best concentration to stimulate callus formation from stem explants of W. biflora with the fastest response (10 d), the highest biomass of callus (55 mg dry weight) and the best callus characteristic (green and compact). Application of 4% (w/v) sucrose in MS medium enhanced callus formation along with callus biomass and stigmasterol production (88 mg g-1) compared with the control (58.3 mg g-1) and in vivo grown stem (53.4 mg g-1). Production of stigmasterol from W. biflora with reduced production time and cost is now possible with the methods obtained from the current study.